Frequency down-conversion of a chirped Ti:sapphire laser pulse with BaWO4 Raman shifter and second-order nonlinear crystal. (1st September 2022) - Kinyaevskiy, I O; Koribut, A V; Grudtsyn, Ya V; Seleznev, L V; Kovalev, V I; Pushkarev, D V; Dunaeva, E E; Ionin, A A
Abstract: We experimentally carried out frequency conversion of a chirped and stretched up to 200 ps near-IR 90 fs Ti:Sapphire laser pulse into the mid-IR through difference frequency generation in either GaSe or LiGaS2 crystal. The crystal was pumped by laser radiation that passed through a BaWO4 crystal, where Stokes frequency-shifted radiation (signal wave) was generated through SRS. The generated ∼60 nJ mid-IR pulse had a central wavelength of 11.1 μ m and FWHM spectral width of about 0.2 μ m, which made it possible to achieve a pulse duration of ∼0.9 ps after its compression. The mid-IR pulse generation efficiency was ∼10 −3 % at SRS efficiency of 3%. To the best of our knowledge, this all solid-state scheme combining Raman shifting and second-order nonlinear crystals achieves the frequency down-conversion of femtosecond near-IR laser pulses to ∼11 μ m radiation for the first time.